Evaluation the Potential of Onion/Laponite Composites Films for Sustainable Food Packaging with Enhanced UV Protection and Antioxidant Capacity - Barbosa, Maciel L.; Oliveira, Leticia M. de; Paiva, Robert; Dametto, Alessandra C.; Dias, Diogenes dos S.; Ribeiro, Clovis A. [UNESP]; Wrona, Magdalena; Nerín, Cristina; Barud, Hernane da S.; Cruz, Sandra A. (MDPI, 2023)
Agro-industrial residues have attracted attention for their applications in the field of biodegradable packaging. Recently, our research group has developed onion-based films with promising properties for this type of application due to their non-toxicity, biocompatibility and biodegradability. Therefore, in this study, we investigated the effect of Laponite clay concentration on the physicochemical and antioxidant properties of the onion-based films, which were prepared by a casting method. The XRD and FTIR data confirm the presence of the mineral clay in the onion-based films. These findings are consistent with those obtained from FE-SEM analysis, which revealed the presence of typical Laponite grains. In terms of wettability, the results show that the clay decreases the hydrophilic character of the material but slightly increases the water vapor permeation. Optical characterization revealed that the materials exhibited zero transmittance in the UV region and increased opacity in the visible region for composites containing 5% and 10% Laponite. Furthermore, the antioxidant test demonstrated higher antioxidant potential in the composites compared to the pure films. Consequently, these results suggest that the formation of Laponite and onion composites could be an essential strategy for developing natural polymers in the field of food contact packaging.
Keywords: antioxidant; biopolymer; composite; laponite; onion films